Non-Invasive Assessment of Non-Alcoholic Fatty Liver Disease: Ultrasound and Transient Elastography - Berzigotti, Annalisa (Reviews on Recent Clinical Trials, 2014)
Non-alcoholic fatty liver disease (NAFLD) is extremely prevalent in the Western world. Non-invasive diagnostic methods should be able to reflect the presence and severity of liver fatty changes and the presence and severity of hepatic inflammation and fibrosis (features of non-alcoholic steato-hepatitis), since these are related to the risk of progression and clinical complications. This article will: a) review the rational basis for the use of ultrasound and transient elastography in patients with NAFLD; b) summarize available data regarding the diagnostic performance of these two widely used non-invasive imaging methods in patients with NAFLD; and c) give an overview of newer sonographic applications that might be used in clinical practice in the near future in this field.
Keywords: controlled attenuation parameter